A clinicopathological study of 39 cases of atypical polypoid adenomyoma of the uterus - Honglan Zhu; Taji Bai; Zhao Tian; Shanshan Lu; Dongmei Bao; Heng Cui (BMJ Publishing Group, 2021)
Objective: To clarify the clinical and pathological characteristics of atypical polypoid adenomyoma (APA) in order to improve the criteria used to diagnose and treat this disease. Study design: In 39 cases of APA, retrospective analysis was performed of theclinical data, pathological characteristics, and the follow-up findings in patients admitted to the Peking University People's Hospital from 2007 to 2019. Results: The median age was 39.6 years (range 24-60 years). Thirty seven patients were premenopausal (i.e.94.9 ​%) and eighteen patients were nullipara (i.e. 46.2 ​%). Abnormal uterine bleeding was the most common presenting symptom. Hysteroscopic transcervical resection (i.e.TCR) identified lesions in 35 cases whereas: a) hysterectomy identified them in 3 cases; b) dilatation and curettage (D&C) identified them in 1 case. Immunohistochemical analysis was performed on 24 samples. In the glandular component, hormone receptors were positively expressed. In all cases, Ki67 expression was detectable in approximately 50 ​% of the cases. In those samples, its presence was definitive in eighteen of the nineteen cases (94.7 ​%,18/19), p53 positive expression was present in most cases (68.8 ​%,11/16), and PTEN positive expression was detected in 40 ​% (4/10). Stroma immunophenotype expression was exhibited as follows: a)CD10-(12/12), Desmin +(6/7); b) Vimentin +(4/4); c) α-SMA+ (3/3) and; d) p16 positve staining in of 80 ​%(4/5).The concurrent amount of atypical endometrial hyperplasia with atypical polypoid adenomyoma was 23.1 ​%(9/39), while its concurrent level of endometrial carcinoma with atypical polypoid adenomyoma was 7.7 ​% (3/39). Fertility preserving treatments were performed in 20 patients with strong childbearing desires. Their pregnancy success was 15 ​%(3/20) and the live birth frequency was 10 ​%(2/10). Follow-up findings were available in 36 cases (92.3 ​%) with a medial follow-up of 48.1 months (range 4-122 months). Its pathological recurrence and frequency of progression into endometrial carcinoma were both 5 ​%(1/20). One case died of another type of malignancy, while the other patients were alive. Conclusions: APA occurs mostly during the years of a women's reproductive period. Its diagnosis is based on the analysis of pathological and immunohistochemical findings. Individuals diagnosed with APA are at risk to coexist with endometrial carcinoma and atypical endometrial hyperplasia. For those individuals who desire retaining fertility, the treatment strategy involves performing TCR completely remove the lesions and close follow-up for surveillance of possible progressive APA recurrence. For those individuals who have no fertility desire, hysterectomy may be a preferred option.